A comparison of postoperative respiratory complications associated with the use of desflurane and sevoflurane: a single‐centre cohort study. (3rd August 2020) - Zucco, L.; Santer, P.; Levy, N.; Hammer, M.; Grabitz, S. D.; Nabel, S.; Ramachandran, S. K.
Summary: Sevoflurane and desflurane are the most commonly used volatile anaesthetics for maintenance of anaesthesia. In this study, we aimed to evaluate the relationship between choice of volatile anaesthetic and early postoperative respiratory complications, and to address a critical knowledge gap in safety outcomes between these two commonly used agents. We performed a retrospective analysis of adult (non‐cardiac surgery) patients who received sevoflurane or desflurane for the maintenance of general anaesthesia at our institution between 2005 and 2018. We evaluated the association between desflurane exposure (when compared with sevoflurane) and the primary outcome of postoperative respiratory complications, defined by early post‐extubation desaturation (Sp O2 < 90%) or re‐intubation within 7 days postoperatively. Multivariable regression analyses were performed and adjusted for confounding factors, including patient, anaesthetic and surgical factors. Propensity matched, interaction and sub‐group analyses were performed to assess outcomes in high‐risk groups: morbidly obese (BMI > 35 kg.m −2 ); elderly (age > 65 years); and high risk of respiratory complications as well as the primary outcome at 24 h. Desflurane was used for 23, 830 patients and sevoflurane for 84, 608 patients. Patients exposed to desflurane did not demonstrate a reduced risk of postoperative respiratory complications when compared with sevoflurane (adjusted odds ratio 0.99, 95%CI 0.94–1.04, p = 0.598). These findings were consistent across all sub‐groups of high‐risk patients and in the propensity score matched cohort. In summary, desflurane use was not associated with reduced postoperative respiratory complications when compared with sevoflurane. In the context of environmental and cost concerns with volatile anaesthetic agents, our study provides important data to support organisational decisions regarding the use of desflurane.